IMPLEMENTASI PENGUATAN PERILAKU WIRAUSAHA SISWA MELALUI PROGRAM MARKET DAY DI SD NEGERI 3 ADIPASIR, BANJARNEGARA - Citra Mukti, Restiana; Andriani, Ana (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2024)
Education is an important place for the formation of student behavior and character. Market day is present as a form of implementation of entrepreneurial learning that supports aspects of student competence that are instilled through entrepreneurial values. This research was conducted at SD Negeri 3 Adipasir Rakit, Banjarnegara using a qualitative approach method aimed at describing the implementation of strengthening students' entrepreneurial behavior. The research results show that the market day program is a strong foundation for strengthening entrepreneurial behavior. The planning stage is the main foundation, where students are invited to formulate ideas, produce goods, set goals, and develop implementation strategies. Market day forms various entrepreneurial attitudes. Students demonstrate independence, creativity, leadership, honesty, curiosity, discipline, cooperation and innovation during activities. Market day is not only an ordinary school event, but also a forum for strengthening students' character and entrepreneurial skills.